2018
DOI: 10.1155/2018/4546896
|View full text |Cite
|
Sign up to set email alerts
|

Small Object Detection with Multiscale Features

Abstract: The existing object detection algorithm based on the deep convolution neural network needs to carry out multilevel convolution and pooling operations to the entire image in order to extract a deep semantic features of the image. The detection models can get better results for big object. However, those models fail to detect small objects that have low resolution and are greatly influenced by noise because the features after repeated convolution operations of existing models do not fully represent the essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…In general, the object detection model detects objects using features extracted through the backbone network, and VGGNet, ResNet, and DenseNet are mainly used as the backbone networks [37][38][39][40]. When VGGNet or ResNet is used as a backbone network, features of several layers are often fused to detect small objects [10,41]. However, DenseNet utilizes all of the features from the previous layer in each layer, it was found that the process of selecting a layer for feature fusion could be In general, the object detection model detects objects using features extracted through the backbone network, and VGGNet, ResNet, and DenseNet are mainly used as the backbone networks [37][38][39][40].…”
Section: Training and Validation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the object detection model detects objects using features extracted through the backbone network, and VGGNet, ResNet, and DenseNet are mainly used as the backbone networks [37][38][39][40]. When VGGNet or ResNet is used as a backbone network, features of several layers are often fused to detect small objects [10,41]. However, DenseNet utilizes all of the features from the previous layer in each layer, it was found that the process of selecting a layer for feature fusion could be In general, the object detection model detects objects using features extracted through the backbone network, and VGGNet, ResNet, and DenseNet are mainly used as the backbone networks [37][38][39][40].…”
Section: Training and Validation Methodsmentioning
confidence: 99%
“…However, DenseNet utilizes all of the features from the previous layer in each layer, it was found that the process of selecting a layer for feature fusion could be In general, the object detection model detects objects using features extracted through the backbone network, and VGGNet, ResNet, and DenseNet are mainly used as the backbone networks [37][38][39][40]. When VGGNet or ResNet is used as a backbone network, features of several layers are often fused to detect small objects [10,41]. However, DenseNet utilizes all of the features from the previous layer in each layer, it was found that the process of selecting a layer for feature fusion could be omitted and the features of the ships could be better extracted.…”
Section: Training and Validation Methodsmentioning
confidence: 99%
“…Conventional object detection (OD) methods are not suitable to detect small objects, because they use very deep depth networks with pooling operations for feature extraction [46,47,48,49,50]. For example, Faster-RCNN employs anchor boxes to extract object candidate regions from a feature map.…”
Section: Proposed Traffic Light Recognition Methodsmentioning
confidence: 99%
“…The discriminator, however, competes with the generator to identify the representation generated by the generator and allows the generator to have a representation that is useful for detection. Hu et al [36] proposed a way to use the features extracted from other levels of features. Bosquet et al [37] proposed the problem of a loss of target information as existing detector networks undergo downsampling.…”
Section: Related Workmentioning
confidence: 99%